Characteristics and in‐hospital outcomes of patients requiring aeromedical retrieval for pregnancy, compared to non‐retrieved metropolitan cohorts. (10th January 2021) - Gardiner, Fergus W.; Richardson, Alice; Roxburgh, Carly; Gillam, Marianne; Churilov, Leonid; McCuaig, Ruth; Carter, Sean; Arthur, Christopher; Wong, Cynthia; Morton, Adam; Callaway, Leonie; Lust, Karin; et al.
Abstract : Background: Limited access to obstetrics and gynaecology (O&G) services in rural and remote Australia is believed to contribute to suboptimal birth outcomes. Aims: To describe the characteristics of pregnancy aeromedical transfers, in‐hospital outcomes, and patient access to O&G services, as compared to whole of Australia data. Materials and methods: We conducted a cohort study of women who required aeromedical retrieval for pregnancy‐related issues between the 1 January 2015 and 31 December 2017. Results: Hospital outcome data were collected on 2171 (65.2%) mothers and 2438 (100.0%) babies. The leading retrieval reason was threatened preterm labour and delivery ( n  = 883; 40.7%). Most patients were retrieved from rural and remote areas ( n  = 2224; 93.0%). Retrieved patients were significantly younger (28.0 vs 30.0 years, 95% CI 27.7–28.3), more likely to be overweight or obese (52.2% vs 45.1%, 95% CI 47.5–56.9) and to have smoked during their pregnancy (14.0% vs 9.9%, 95% CI 12.5–15.5) compared to Australian pregnant women overall. Over one‐third of transferred women gave birth by Caesarean section ( n  = 812; 37.4%); the median gestational age at birth was 33.0 (95% CI 32.7–33.3) weeks. Early gestation is associated with low birth weights (median = 2579.5 g; 95% CI 2536.1–2622.9), neonatal resuscitation (35.4%, 95% CI 33.5–37.3), and special care nursery admission (41.2%, 95% CI 39.3–43.2). There were 42 (1.7%, 95% CI 1.2–2.2) stillbirths, which was significantly higher than seen Australia‐wide ( n  = 6441; 0.7%). Conclusion: This study found that pregnant women retrieved by the Royal Flying Doctor Service were younger, with higher rates of obesity and smoking.